SMALL AND MEDIUM ENTERPRISES AND ENVIRONMENTAL ISSUES: EMPIRICAL EVIDENCES IN ITALIAN CONTEXT - Balluchi, Federica; Furlotti, Katia (European Scientific Journal, ESJ, 2013)
Social and environmental issue related to companies activity has received growing attention over the last few years; it represents a voluntary approach taken by an enterprise to meet stakeholdersâ€™ expectations, considering their different features. Small and Medium Enterprises (SMEs) have begun to show a strong sensitivity towards social and environmental responsibility: the very nature of SMEs does indeed, by and of itself, imply a clear â€œsocially-orientedâ€ dimension; SMEs are deeply rooted in the local communities and many entrepreneurs instinctively understand that behaving correctly towards their employees, suppliers, the community and the surrounding environment represents a strong competitive factor. Unfortunately, this frequently fails to translate into careful planning and structuring of their socially-oriented activities, and into an adequate accountability process. In this sense, they need to formalize and add extra value to the CSR choices and to all the behaviours and strategies that would qualify the company to this end. In the light of this, the paper aims to investigate the degree of awareness, attention and sensitivity that a sample of Italian SMEs pays towards the social responsibility and, in particularly, towards environmental aspect. The study will be conducted by questionnaire on around 3,180 small enterprises. From a methodological point of view, the research is divided into three main steps: 1) theoretical and empirical framework on SMEs and CSR; 2) empirical research: method; recording of data; analysis and interpretation of data; 3) conclusions, limits and further discussions.